Protection strategy for multi‐terminal high‐voltage direct current grids using SFCLs at converter station output. Issue 15 (11th September 2018) - Leon Garcia, William Ricardo; Bertinato, Alberto; Tixador, Pascal; Raison, Bertrand; Luscan, Bruno
Abstract : This study proposes a non‐selective protection strategy for multi‐terminal high voltage direct current grids based on resistive‐type superconducting fault current limiters (SFCLs). Located at the output of AC/DC converters, the SFCL limits the current contribution from the AC grid in case of DC fault. With this approach, the fault clearing time constraint is relieved allowing the use of mechanical DC circuit breakers for fault current interruption. Furthermore, the breaking capability and energy dissipation requirements of the breaker are greatly reduced. To achieve a fast restoration of the DC grid, a redundant SFCL is introduced in parallel to those in operation, bypassing them when the fault is effectively suppressed. In addition, primary and back‐up protection schemes are described and tested using a three‐terminal bipolar high voltage direct current (HVDC) grid based on half‐bridge modular multilevel converters and cable transmission. Simulations are implemented in EMTP‐RV ® to analyse and discuss performances of the proposed fault clearing strategy.